Ocimum sanctum, Zingiber officinale, and Piper nigrum extracts and their effects on gut microbiota modulations (prebiotic potential), basal inflammatory markers and lipid levels: oral supplementation study in healthy rats - Narendra Babu Kondapalli; Rajkumar Hemalatha; Satyanarayana Uppala; Srinivas Reddy Yathapu; Shujauddin Mohammed; Mullapudi Venkata Surekha; Ananthan Rajendran; Dinesh Kumar Bharadwaj (Taylor & Francis Group, 2022)
Context Ocimum sanctum Linn (Labiatae) (OS), Zingiber officinale Rose (Zingiberaceae) (ZO), and Piper nigrum Linn (Piperaceae) (PN) are used in traditional medicine as immunomodulator, anti-inflammatory, and bioavailability enhancer agents. Objective Active phytoconstituents of OS, ZO, PN hydro-alcoholic extracts and their effects on gut microbiota, basal inflammation and lipid profile were investigated in rats. Materials and methods Active phytoconstituents of extracts were analysed using HPLC and GC-MS. SD rats were supplemented with individual/combined extracts (OS-850; ZO-500; PN-100 mg/kg Bw) and Fructooligosaccharide (standard prebiotic-5g/kg-Bw), orally for 30 days. Haematology, lipid profile, LPS, CRP, IL-6, insulin and histology of vital organs were analysed. Caecal bacterial levels were assessed by RT-PCR. Results High content of phenolic compounds luteolin-7-O-glucoside (430 ± 2.3 mg/100g), gallic acid (84.13 ± 1.2 mg/100 g) and flavones (88.18 ± 1.8 mg/100 g) were found in OS, ZO, and PN, respectively. Combined extract was rich in luteolin-7-O-glucoside (266.0 ± 1.80 mg/100 g). Essential oils including methyleugenol (13.96%), 6-shogaol (11.00%), piperine (18.26%), and cyclopentasiloxane (10.06%) were higher in OS, ZO, PN and combined extract. Higher levels of caecal Lactobacillus (1.7-3.4-fold), Bifidobacterium (5.89-28.4-fold), and lower levels of Firmicutes (0.04-0.91-fold), Bacteroides (0.69-0.88-fold) were noted among extracts and FOS supplemented rats. Significant (p < 0.05) decrease in plasma lipid profile and LPS was noted in all supplemented rats. Discussion and conclusions The current study could be first of its kind in exploring prebiotic potential of OS, ZO, PN and their effect on native gut bacterial population.